Novel Organic Mineral Complex Prevents High-Fat Diet-Induced Changes in the Gut and Liver of Male Sprague-Dawley Rats. (18th December 2020) - Crawford, M. S.; Mohr, A. E.; Sweazea, K. L.
Abstract : Diet-induced obesity and metabolic syndrome are associated with the onset of gastrointestinal diseases, such as hepatic steatosis and gut inflammation. Prior research shows that a proprietary soil-derived organic mineral complex (OMC) prevents hyperglycemia, endotoxemia, and liver injury in rats fed a high-fat diet (HFD) for 10 weeks. The aim of this study was to further examine the effects of OMC on the liver and gastrointestinal health of these rats. Six-week-old male Sprague-Dawley rats ( n = 36) were divided into two dietary groups: Chow or HFD fed for 10 weeks. Animals were further divided ( n = 6/group) and administered 0, 0.6, or 3.0 mg/mL OMC in their drinking water. The 10-week HFD resulted in significant liver fat accumulation. Both OMC doses prevented hepatic increases in the glycation end product N ε -(carboxymethyl)lysine (CML) induced by HFD (p < 0.05 ). Low-dose OMC was associated with higher expression of occludin in the small intestine of rats fed either diet (two-way ANOVA, p < 0.042 ). Linear discriminant analysis (LDA) effect size (LEfSe) indicated significant differences in fecal microbial composition of untreated HFD-fed rats in comparison to untreated Chow rats at 10 weeks (LDA score > 2.0 : 18). After 10 weeks, untreated HFD-fed rats were also more abundant in bacteria associated with obesity and metabolic disease in comparison to corresponding week 0 samples (LDA score > 2.0 : 31), 10-week untreated Chow (LDA > 2.0 : 18), or 10-week OMC-treated HFD-fed rats (0.6 mg/mL; LDA > 2.0 : 80, 3.0 mg/mL; LDA > 2.0 : 8). Low-dose OMC prevented the HFD-induced increase in the Firmicutes-to-Bacteroidetes (F/B) ratio (p < 0.0416 ). Study animals treated with OMC exhibited no significant changes in the gut microbiota at week 10, although gut inflammatory biomarkers were not significantly altered by diet or OMC treatment. These results indicate that OMC supplementation ameliorates glycosylation reactions and modifies HFD-induced alterations in the intestinal microbiota.